Computer simulation of diamond-wire cutting of hard and abrasive rock - A. Bortolussi; R. Ciccu; P. P. Manca; G. Massacci (The Institute of Materials, Minerals and Mining, 1994)
Tool performance and the unit cost of cutting depend on a number of operational variables (peripheral velocity, pull-back force, water injection rate, angles of the sections of wire outside the rock) as well as on the geometric features of the cut itself (area and shape). Cutting rate and wire productivity are also influenced by the type and number of diamond beads per unit length of wire and by the characteristics of the rock (granite or marble). A computer program aimed at handling a problem of this complexity has been developed and tested with the use of available field and laboratory data and has been found acceptably reliable. Discrepancies between current industrial data and some of the results suggest future lines of research, while the simulation should also be extended to include different types of rock and tool and a variety of bench face geometries